Fish (Labeo rohita) scales as potential low-cost biosorbent for removal of Malachite Green from aqueous solutions - Chowdhury, S.; Das Saha, P.; Ghosh, Ujjal (Taylor and Francis Group, 2012)
The feasibility of using fish (Labeo rohita) scales as low-cost biosorbent for the removal of hazardous Malachite Green (MG) dye from aqueous solutions was investigated. Employing a batch experimental setup, the effect of operational parameters such as biosorbent dose, initial solution pH, contact time, and temperature on the dye removal process was studied. The equilibrium biosorption data followed both Langmuir and Freundlich isotherm models, whereas the experimental kinetic data fitted well to the pseudo-second-order kinetic model. Thermodynamic study indicated spontaneous and endothermic nature of the biosorption process. The results suggest that fish scales could be used as an effective biosorbent for removal of MG dye from aqueous solutions.